2005
DOI: 10.1103/physrevb.72.174407
|View full text |Cite
|
Sign up to set email alerts
|

Distinct order of Gd4fand Fe3dmoments coexisting inGdFe

Abstract: Single crystals of flux-grown tetragonal GdFe4Al8 were characterized by thermodynamic, transport, and x-ray resonant magnetic scattering measurements. In addition to antiferromagnetic order at TN ≈ 155 K, two low-temperature transitions at T1 ≈ 21 K and T2 ≈ 27 K were identified. The Fe moments order at TN with an incommensurate propagation vector (τ, τ, 0) with τ varying between 0.06 and 0.14 as a function of temperature, and maintain this order over the entire T < TN range. The Gd 4f moments order below T2 w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In continuation to our studies in the RET 4 X 8 family and related compounds in this series, we found that EuAg 4 In 8 exists in tetragonal phase as well. The other motivation of this work is that the compounds having general formula RET 4 X 8 (RE¼La-Nd, Sm-Lu and U; T¼Cr, Mn, Fe, Cu and Ag; X¼ Al, Ga and In) are generally well known for their interesting physical properties like high temperature antiferromagnetic ordering (T N ) in GdFe 4 Al 8 [30] (T N ¼155 K) along with two low temperature transitions at T 1 ¼ 21 K and T 2 ¼27 K, high temperature magnetic ordering (163.5 K) in TbFe 4 Al 8 [31], anisotropic magnetic properties of single crystals of UFe 4 Al 8 [32] and the antiferromagnetic-paramagnetic transitions at T N ¼6.50 and 6.75 K in GdCr x Al 12À x (x¼ 3.5 and 4.0) [33].…”
Section: Introductionmentioning
confidence: 99%
“…In continuation to our studies in the RET 4 X 8 family and related compounds in this series, we found that EuAg 4 In 8 exists in tetragonal phase as well. The other motivation of this work is that the compounds having general formula RET 4 X 8 (RE¼La-Nd, Sm-Lu and U; T¼Cr, Mn, Fe, Cu and Ag; X¼ Al, Ga and In) are generally well known for their interesting physical properties like high temperature antiferromagnetic ordering (T N ) in GdFe 4 Al 8 [30] (T N ¼155 K) along with two low temperature transitions at T 1 ¼ 21 K and T 2 ¼27 K, high temperature magnetic ordering (163.5 K) in TbFe 4 Al 8 [31], anisotropic magnetic properties of single crystals of UFe 4 Al 8 [32] and the antiferromagnetic-paramagnetic transitions at T N ¼6.50 and 6.75 K in GdCr x Al 12À x (x¼ 3.5 and 4.0) [33].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds having general formula RET 4 X 8 (RE = La–Nd, Sm–Lu, and U; T = Cr, Mn, Fe, Co, Cu, and Ag; X = Al, Ga, and In) have been reported for their interesting physical properties. For example, high-temperature antiferromagnetic ordering ( T N ) observed in GdFe 4 Al 8 ( T N = 155 K) in addition to the two low-temperature magnetic transitions at T 1 = 21 K and T 2 = 27 K, high-temperature magnetic ordering (163.5 K) in TbFe 4 Al 8 , anisotropic magnetic properties on the single crystals of UFe 4 Al 8 , and some more compounds are reported in the REFe 4 Al 8 family. The antiferromagnetic–paramagnetic transitions are observed in GdCr x Al 12– x at T N = 6.50 and 6.75 K for x = 3.5 and 4.0, respectively …”
Section: Introductionmentioning
confidence: 99%